Atrial cardiopathy is associated with cerebral microbleeds in ischemic stroke patients - Zhao, David X.; Gootee, Emma; Johansen, Michelle C. (Frontiers in Neurology, 2022)
Objective Cerebral microbleeds (CMB) are small accumulations of hemosiderin associated with cerebrovascular risk factors, but whether they are associated with atrial cardiopathy is not known. The goal of this study is to determine, among ischemic stroke patients, the association between study-defined atrial cardiopathy and CMB presence, location, and number. Methods Ischemic stroke patients admitted to Johns Hopkins (2015–2019) with transthoracic echocardiography and electrocardiography were included. Cerebral microbleeds were defined as small, round hypo-intensities on T2* susceptibility weighted imaging or gradient recalled echo magnetic resonance imaging sequences. Atrial cardiopathy was defined as the presence of ≥1: left atrium diameter >4.0 cm (males) or >3.8 cm (females), PR interval >200 ms, or N-terminal pro-B-type natriuretic peptide >250 pg/ml. Binary/Ordinal logistic regression models were used to determine the association between atrial cardiopathy, and cerebral microbleed presence, location (lobar/deep), or number, each, adjusted for potential confounders. Results Patients (N = 120) were mean age 60 years (range 22–98), 46% female, 62% black, and 39% were on anti-thrombotic medication at time of admission. 39 (32%) participants had ≥1 cerebral microbleeds. Forty-six (38%) patients had atrial cardiopathy. Atrial cardiopathy was associated with higher odds of having cerebral microbleeds (OR 2.50, 95% CI 1.02–6.15). Atrial cardiopathy was associated with lobar cerebral microbleeds (OR 2.33, 95% CI 1.01–5.37) in univariate analysis but not with deep cerebral microbleeds (OR 0.45, 95% CI 0.13–1.54), with neither association significant after adjustment. There was no difference in risk of having 1 vs. no cerebral microbleeds (RRR 2.51, 95% CI 0.75–8.37) and >1 cerebral microbleed vs none (RRR 2.57, 95% CI 0.87–7.60) among those with atrial cardiopathy. Conclusions Atrial cardiopathy is associated with the presence, but not burden, of cerebral microbleeds in ischemic stroke patients. We cautiously suggest that atrial cardiopathy, either directly or through shared vascular risk, may contribute to the presence of CMB.